PENGARUH LATIHAN ZIG-ZAG RUN DAN LADDER DRILL TAPS TERHADAP KECEPATAN TENDANGAN SABIT UKM PENCAK SILAT UNWAHAS 2023 - Catur Wahyu Priyanto; Fatkulmanan; Miftachul A’la (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
Unwahas pencak silat athletes have poor sickle kick speed, because every sickle kick attack is easily anticipated by the opponent, one of the training methods to increase sickle kick speed is zig-zag run and ladder drill taps. So this study aims to determine the effect zig-zag run and ladder drill taps exercises on sickle kick speed of Unwahas pencak silat athletes. This research is an experimental research with a quantitative approach. zig-zag run and ladder drill taps exercises are carried out four weeks and three times each week. The population in this study were 40 UNWAHAS pencak silat athletes. Sampling using purposive sampling, namely the sampling technique according to the criteria. The study was conducted in May-June and the number of samples taken was 10 people. The results showed that: (1) there was a significant effect of zig-zag run training with the results of the t test with a Sig (2-tailed) value of right crescent 0.000 and crescent left with a Sig (2-tailed) value of 0.000 where the p value <0.05 means that there is a significant effect. (2) there is a significant effect of the ladder drill taps exercise by obtaining a t test value of sig (2-tailed) 0.001 right sickle, and obtaining a Sig (2- tailed) value of 0.001 left sickle where the p value <0.05 means that there is a significant effect . (3) there is more influence which exercise is more effective by finding the difference or the mean results of the two groups, by obtaining the results of the comparison of the average value of zig-zag run = 23.00, ladder drill taps average value of 20.90, so zig-zag zag run > ladder drill taps. Thus it can be concluded that the zig-zag run exercise and ladder drill taps both have an effect on the sickle kick speed of Unwahas UKM pencak silat athletes, but there is something that is more influential on the sickle kick speed of Unwahas UKM pencak silat athletes, namely by using the zig-zag run exercise